2008
DOI: 10.1089/ten.teb.2007.0435
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin: A Versatile Scaffold for Tissue Engineering Applications

Abstract: Tissue engineering combines cell and molecular biology with materials and mechanical engineering to replace damaged or diseased organs and tissues. Fibrin is a critical blood component responsible for hemostasis, which has been used extensively as a biopolymer scaffold in tissue engineering. In this review we summarize the latest developments in organ and tissue regeneration using fibrin as the scaffold material. Commercially available fibrinogen and thrombin are combined to form a fibrin hydrogel. The incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
446
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 853 publications
(455 citation statements)
references
References 184 publications
4
446
0
5
Order By: Relevance
“…155 Proteins delivered to the site of an injury via blood, such as fibrin and fibrinogen, have also been investigated as scaffold materials for their hemostatic and cell-binding capacity. 157 Several other naturally derived polymers such as silkworm silk fibers exhibit comparable biocompatibility in vitro and in vivo as compared with other commonly used biomaterials such as collagen and polylactic acid (PLA). 158 Despite the optimism surrounding this approach, several important barriers remain in the pursuit towards utilizing full-length natural proteins for the construction of in 3D scaffolds.…”
Section: Chemical Effectors In Synthetic Bone Scaffoldsmentioning
confidence: 99%
“…155 Proteins delivered to the site of an injury via blood, such as fibrin and fibrinogen, have also been investigated as scaffold materials for their hemostatic and cell-binding capacity. 157 Several other naturally derived polymers such as silkworm silk fibers exhibit comparable biocompatibility in vitro and in vivo as compared with other commonly used biomaterials such as collagen and polylactic acid (PLA). 158 Despite the optimism surrounding this approach, several important barriers remain in the pursuit towards utilizing full-length natural proteins for the construction of in 3D scaffolds.…”
Section: Chemical Effectors In Synthetic Bone Scaffoldsmentioning
confidence: 99%
“…Collagen peptides have also been used, with preclinical data demonstrating increased collagen synthesis [129], maintenance of homeostasis [130] and improved healing, as judged by mean average diameter, distribution of fibrils and GAG composition [131]. The utilisation of fibrin has been advocated based on its high cytocompatibility, biodegradability, controllable cross-linking, carrier capacity and presence of several ECM proteins, such as fibronectin, that enhance cell adhesion and proliferation [132][133][134]. Preclinical analysis revealed that fibrin glue around the suture site enabled rabbit flexor tendon healing with smooth gliding surface and without formation of adhesions [119].…”
Section: Minimally Invasive Strategies For Small Tendon Injuriesmentioning
confidence: 99%
“…However, they might not be the more appropriate for tissue engineering. Indeed, according to Ahmed et al, fibrin hydrogels as cell scaffold for tissue engineering have three major disadvantages: matrix shrinkage, low mechanical stiffness, and rapid degradation before proper tissue formation [2]. The translucent gels, though not supporting cell proliferation, were able to maintain the initial cell number and to sustain cell survival up to 3 weeks of culture without noticeable carrier shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Since many years, fibrin glues have been widely used as surgical sealants. More recently, they also have been proposed as scaffolding for cell delivery in several tissue engineering applications [2]. Numerous in vitro studies, indeed, have demonstrated the ability of fibrin gels to support survival, proliferation, and/or differentiation of many cell types [3][4][5][6], including mesenchymal stromal cells (MSCs) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%